ANALISIS FERTILITAS PENDUDUK: PROVINSI BENGKULU - Heri Sunaryanto (Jurnal Kependudukan Indonesia, 2012)
The population problem in Bengkulu has been critical, characterized by higher rates of population growth and fertility than in Indonesia as a whole. The aims of this study are to analyze comprehensively and give a full description of the trends of population changes in Bengkulu in terms of size, fertility and the sociodemographic characteristics of the population. The method used is descriptive analytic through use of secondary data from the 2010 Indonesian Population Census, the 2007 Indonesian Health and Demography Survey, and the Mini Survey from theBKKBN. The result of the study points out that since 1970 the size of the population in Bengkulu has increased significantly (three times from 1970 to 2010) due to transmigration and family planning programs during the Soeharto era, but not in the Reformation era. The high political will and the success of the family planning program under the Soeharto government had decreased significantly the rate of population growth and fertility until 2010. The study also finds that some micro factors such as educational attainment, economic conditions and the status of the population dwelling (rural or urban area) did not show any correlation with the fertility rate in Bengkulu. The implication of this result is that the awareness of the family planning program needs to be improved and become a challenge for related institutions such as theBKKBN in the new democratized era.Key Words: fertility, population growth rate, Bengkulu Province